2014
DOI: 10.5937/gads1449037n
|View full text |Cite
|
Sign up to set email alerts
|

First premolar variations in number of roots, root canals and tooth length

Abstract: 1 Medicinski fakultet u Nišu, Klinika za stomatologiju, Odeljenje za Bolesti zuba i endodonciju 2 Studenti doktorskih studija medicinskog fakulteta u Nišu SažetakPoznavanje spoljašnje i unutrašnje morfologije zuba je od velike važnosti za pripadnike svih grana stomatološke prakse. U konzervativnoj stomatologiji je poznavanje spoljašnjih morfoloških karakteristika zubne krune značajno zbog sklonosti odreĎenih grupa zuba ka karijesu i uspešne restauracije u funkcionalnom i estetskom smislu. Uspešan endodontski t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 7 publications
5
6
0
Order By: Relevance
“…Differences in the number of roots and canals are seen in different geographical regions. Previous studies in Serbian population [4,22] reported a similar incidence of one root in maxillary first premolars as our study (43% and 46.3%, respectively) by using clearing and staining techniques. A study conducted in Spanish population showed similar results, where one root was present in 46% [26].…”
Section: Maxillary Premolarssupporting
confidence: 87%
See 4 more Smart Citations
“…Differences in the number of roots and canals are seen in different geographical regions. Previous studies in Serbian population [4,22] reported a similar incidence of one root in maxillary first premolars as our study (43% and 46.3%, respectively) by using clearing and staining techniques. A study conducted in Spanish population showed similar results, where one root was present in 46% [26].…”
Section: Maxillary Premolarssupporting
confidence: 87%
“…In previous studies, a variety of methods were used for evaluating the internal morphology of teeth in laboratory and clinical settings [4,9,11,13,15,[18][19][20][21][22][23][24]. Laboratory methods are highly accurate, whereas the clearing and staining technique is considered the gold standard in assessing root canal morphology, but their implementation requires tooth extraction [4]. In the last decade, the CBCT was often used to study anatomical and morphological characteristics of root canals in clinical settings [3,7,8,10,12,14,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations